Perlindungan Hukum Terhadap Investor Berdasarkan Prinsip Keterbukaan oleh Emiten di Pasar Modal - I Nengah Suardana; Ni Luh Mahendrawati; Ni Gusti Ketut Sri Astiti (Fakultas Hukum Universitas Warmadewa, 2020)
Capital markets are defined as markets or meeting places for sellers and buyers who trade long-term securities such as stocks and bonds. Capital markets activities are complicated, legal instruments are needed to regulate them so that the market runs regularly, fairly, and fairly for all parties. On that basis, the capital market law was born (securities law). Capital market law is a legal norm or legal rule that regulates all aspects related to the capital market. The formulation of the problem in this study are 1) How is the legal protection for investors to obtain information disclosure about shares owned in the capital market? 2) What is the principle of disclosure by Issuers in the delivery of information to investors in the capital market? In this study the author uses the normative method. The results of this study are that investors really need information from companies that buy and sell shares in the capital market. The level of capital market efficiency is determined by the availability of information provided by the public company to the investor. Legal protection for investors is preventive and repressive. Where this legal protection relates to the provisions that require guidance, education and supervision from the stock exchange authority as well as sanctions imposed on violators.